Joint Analysis of Transcriptome and Metabolome at Different Leaf Color Stages of Cymbidium sinense 'Red Sun' - Jie GAO; Chuyan XIANG; Junhong ZHAO; Qiming PAN; Fengxi YANG (Guangdong nongye kexue)
【Objective】The study aims to elucidate the change patterns of related genes during the color transition of Cymbidium sinense 'Red Sun', in order to provide guidance for the improvement of C. sinense leaf color.【Method】The Illumina HiSeq high-throughput sequencing platform was used to sequence the red, yellow and green leaves of C. sinense 'Red Sun', analyze the enrichment pathway of differentially expressed genes, and conduct a joint analysis of transcriptome and metabolome data. Key differential genes were also verified by fluorescent quantitative PCR.【Result】The results showed that a total of 861 differentially expressed genes (DEGs) were screened during the transition from red to yellow leaves, with 204 up-regulated genes and 657 down-regulated genes; during the transition from yellow to green leaves, a total of 815 DGEs were screened, with 492 up-regulated genes and 323 down-regulated genes. KEGG pathway enrichment analysis revealed that genes related to pigment synthesis and metabolism were significantly enriched during the color transition process of C. sinense 'Red Sun'. During the leaf color transition, the expression levels of transcription factor families such as MYB, NAC, WRKY, and bHLH showed significant differences. Joint analysis with metabolome data indicated that flavonoids, isoflavonoids, flavones, and flavonols, as well as differential genes and metabolites in the metabolites synthesis pathways, were significantly enriched during the color transition process of C. sinense 'Red Sun'. A total of 26 differentially expressed genes in the flavonoid metabolic pathway were identified, which all showed significant down-regulation during the transition from red to yellow leaves. Additionally, the contents of five differential metabolites were significantly decreased during this transition. During the transition from yellow to green leaves, 17 genes and two metabolites (neohesperidin and naringin chalcone) showed significant differences.【Conclusion】The reduction in the content of anthocyanin synthesis precursors and the expression levels of related synthetic enzyme genes leads to the gradual disappearance of the red color in leaves of C. sinense 'Red Sun', and the high expression of photosynthetic pigment synthesis-related genes is the main reason for the leaves of C. sinense 'Red Sun' changing from yellow to green.